Legal issues in claiming late delivery damage in abandoned housing projects in Peninsular Malaysia - Md Dahlan, Nuarrual Hilal; Md Desa, Md Rejab (2011)
Pursuant to the provisions of the Housing Development (Control and Licensing) Act 1966 and its regulations, particularly the terms in the standard contracts of sale, that if a housing developer fails to complete the construction and to deliver vacant possession of the housing unit purchased by a purchaser within 24 or 36 calendar months, as the case may be, the defaulting housing developer is obligated to pay late delivery damages.Unfortunately, the reverse does not hold true when a housing developer project abandoned the said building development, this provision is of no avail to the purchasers.This is because to trigger the cause of action for claiming late delivery damages, the construction of the houses must be complete and the vacant possession of the units has been delivered to the purchasers.In abandoned housing these condition precedent is absence, i.e there is no complete construction of the unit let alone the delivery of vacant possession of the units.Thus the purchasers would be left in a quandry without any sufficient legal recourse in the wake of the abandoned housing projects' catastrophe.This paper will discuss this difficulty and attempts to put forward certain suggestions to purchasers in claiming late delivery damages and other equitable relief in abandoned housing projects.